Особливості вищої аграрної освіти в Нідерландах - Колесніков, Максим Олександрович; Пащенко, Юлія Петрівна; Kolesnikov, Maksym; Paschenko, Yuliia (Запоріжжя : 2024, 2024)
UA: У роботі розглянуті особливості вищої освіти Нідерландів та аграрної освіти, зокрема. Проведено порівняльний аналіз здобуття освіти в дослідницьких університетах та університетах прикладних наук, охарактеризовано деякі освітні програми університетів Нідерландів. EN: The work considers the peculiarities of higher education in the Netherlands and agricultural education, in particular. A comparative analysis of education at research universities and universities of applied sciences was conducted, some educational programs of universities in the Netherlands were characterized.
The peculiarities of higher agricultural education in the Netherlands
Keywords: вища освіта; Нідерланди; реформування університетської освіти; практичне навчання; higher education; the Netherlands; reforming university education; practical training